2013
DOI: 10.1128/jb.02181-12
|View full text |Cite
|
Sign up to set email alerts
|

SpoIVA and SipL Are Clostridium difficile Spore Morphogenetic Proteins

Abstract: b Clostridium difficile is a major nosocomial pathogen whose infections are difficult to treat because of their frequent recurrence. The spores of C. difficile are responsible for these clinical features, as they resist common disinfectants and antibiotic treatment. Although spores are the major transmissive form of C. difficile, little is known about their composition or morphogenesis. Spore morphogenesis has been well characterized for Bacillus sp., but Bacillus sp. spore coat proteins are poorly conserved i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

17
328
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 141 publications
(345 citation statements)
references
References 50 publications
(95 reference statements)
17
328
0
Order By: Relevance
“…In a sigH mutant, transcription of the opp genes was decreased, while app transcripts were increased, suggesting that the transporters are regulated differently during the adaptation to stationary phase in TY medium (60). However, our transcriptional analysis of app and opp expression in cells grown in sporulation medium (70:30 broth) (36) revealed that the expression of appA and oppB genes increases similarly throughout the transition to stationary phase (see Fig. S2A in the supplemental material).…”
Section: Identification Of Opp and App Transporters In C Difficilementioning
confidence: 72%
See 1 more Smart Citation
“…In a sigH mutant, transcription of the opp genes was decreased, while app transcripts were increased, suggesting that the transporters are regulated differently during the adaptation to stationary phase in TY medium (60). However, our transcriptional analysis of app and opp expression in cells grown in sporulation medium (70:30 broth) (36) revealed that the expression of appA and oppB genes increases similarly throughout the transition to stationary phase (see Fig. S2A in the supplemental material).…”
Section: Identification Of Opp and App Transporters In C Difficilementioning
confidence: 72%
“…To prepare spores for animal studies, strains for spore preparation were grown in BHIS broth overnight and 100 l was spread onto 70:30 agar plates (36). The plates were then incubated for 48 h to allow spores to form.…”
mentioning
confidence: 99%
“…Whole-genome SNP analysis by Illumina next-generation sequencing revealed no additional nucleotide changes in the CD1492 mutant (see Materials and Methods). The CD1492 mutant was tested for the ability to sporulate on 70:30 sporulation agar (27). As demonstrated in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…C. difficile cultures were started in BHIS medium supplemented with 0.1% taurocholate to allow for germination of spores within the starting inoculum and 0.2% fructose to prevent sporulation. When cultures reached an optical density at 600 nm (OD 600 ) of 0.5, 250 l was applied evenly to 70:30 agar medium and incubated anaerobically at 37°C (27). Samples were scraped from the plates at the time points indicated for each experiment and evaluated for sporulation frequency by both phase-contrast counting and enumeration of ethanol-resistant spores.…”
Section: Methodsmentioning
confidence: 99%
“…C. difficile strains were started as lowdensity cultures in BHIS medium supplemented with 0.1% taurocholate (Sigma-Aldrich) and 0.5% fructose and were grown to mid-log phase. Cultures were subsequently back-diluted to an optical density at 600 nm (OD 600 ) of 0.5 in 70:30 sporulation medium (50) or BHIS medium. The cultures were then immediately diluted 1:10 into the main culture flask containing 70:30 or BHIS broth to reach a starting OD 600 of 0.05.…”
mentioning
confidence: 99%